The Effectiveness of Private Forest Institutional and Policy in Banjarnegara and Banyumas Regency - Eva , Eva Fauziyah; Sanudin, Sanudin sanuddin (Forestry Department, University of Muhammadiyah Makassar, 2017)
This research aimed to analyze the effectiveness of institusional and policy on private forest. The research was conducted in Banjarnegara and Banyumas Regency in August 2012 - May 2013. The methods used in this study are structured interview, open interview and Focus Group Discussion (FGD). Assessment of institutional effectiveness was done to government institutional, marketing institututional, and farmer institutional using recommended indicator namely: 1) user and resource boundaries, 2) appropriation and provision, 3) collective-choice arrangements, 4) monitoring, 5) graduated sanctions, 6) conflict-resolution mechanisms, and 7) recognition of appropriators’ rights to organize. The collected data were processed using likert scale and analyzed descriptively. The results showed that effectiveness of institutional in Kabupaten Banjarnegara and Banyumas Regency was moderate condition (quite effective). The effectiveness of private forest policy is seen from four policy viewpoints: policy accuracy, policy implementation, target accuracy, and environmental accuracy. Private forest policy in Kabupaten Banjarnegara is effective based on policy accuracy and environmental accuracy, while private forest policy in Banyumas Regency is effective based on target accuracy and environmental accuracy. This difference in assessment is due to the different of policy or program at the location according to the condition and the desire of community.